Detection of Low Density Lipoprotein—Comparison of Electrochemical Immuno- and Aptasensor - Daria Rudewicz-Kowalczyk (MDPI AG, 2021)
An elevated level of low density lipoprotein (LDL) can lead to the cardiovascular system-related diseases, such as atherosclerosis and others. Therefore, fast, simple, and accurate methods for LDL detection are very desirable. In this work, the parameters characterizing the electrochemical immuno-and aptasensor for detection of LDL have been compared for the first time. An immunosensor has been designed, for which the anti-apolipoprotein B-100 antibody was covalently attached to 4-aminothiophenol (4-ATP) on the surface of the gold electrode. In the case of an aptasensor, the gold electrode was modified in a mixture of ssDNA aptamer specific for LDL modified with –SH group and 6-mercaptohexanol. Square-wave voltammetry has been used for detection of LDL in PBS containing redox active marker, [Fe(CN)6]3−/4−. Our results show the linear dependence of [Fe(CN)6]3−/4− redox signal changes on LDL concentration for both biosensors, in the range from 0.01 ng/mL to 1.0 ng/mL. The limit of detection was 0.31 and 0.25 ng/mL, for immuno- and aptasensor, respectively. Whereas slightly better selectivity toward human serum albumin (HSA), high density lipoprotein (HDL), and malondialdehyde modified low density lipoprotein (MDA-LDL) has been observed for aptasensor. Moreover, the other components of human blood serum samples did not influence aptasensor sensitivity.